A comprehensive microbial analysis of pediatric patients with acute appendicitis - Tsubasa Aiyoshi; Tomo Kakihara; Eiichiro Watanabe; Nao Tanaka; Yusuke Ogata; Hiroaki Masuoka; Rina Kurokawa; Jun Fujishiro; Kouji Masumoto; Wataru Suda (Journal of Microbiology, Immunology and Infection, 2023)
Background: Pathogenesis of pediatric acute appendicitis (AA) is yet to be elucidated. Therefore, we performed a comprehensive microbial analysis of saliva, feces, and appendiceal lumen of AA patients using 16S ribosomal RNA (rRNA) gene amplicon sequencing to elucidate the pathogenesis of pediatric AA. Methods: This study included 33 AA patients and 17 healthy controls (HCs) aged <15 y. Among the AA patients, 18 had simple appendicitis, and 15 had complicated appendicitis. Salivary and fecal samples were obtained from both groups. The contents of the appendiceal lumen were collected from the AA group. All samples were analyzed using 16S rRNA gene amplicon sequencing. Results: The relative abundance of Fusobacterium was significantly higher in the saliva of AA patients as compared to that in HCs (P = 0.011). Bacteroides, Escherichia, Fusobacterium, Coprobacillus, and Flavonifractor were significantly increased in the feces of AA patients, as compared to that in HCs (P = 0.020, 0.010, 0.029, 0.031, and 0.002, respectively). In the appendiceal lumen, Bacteroides, Parvimonas, Fusobacterium, and Alloprevotella were the top bacterial genera with an average relative abundance >5% (16.0%, 9.1%, 7.9%, and 6.0%, respectively). Conclusions: The relative abundance of Fusobacterium was high in the appendiceal lumen of pediatric AA patients. Moreover, the relative abundance of Fusobacterium was significantly higher in the saliva and feces of pediatric AA patients than in those of healthy children. These results suggest that ectopic colonization of oral Fusobacterium in the appendix might play an important role in the pathogenesis of pediatric AA.